History of human impact on Lake Kutubu, Papua New Guinea: The geochemical signatures of oil and gas mining activities in sediments. (April 2016) - Schneider, Larissa; Haberle, Simon G.; Maher, William A.; Krikowa, Frank; Zawadzki, Atun; Heijnis, Henk
Abstract: Lake Kutubu, a large tropical lake in Papua New Guinea, is well known for its ecological importance; however, there have been recent changes to the pristine nature of this lake due to activities associated with the largest oil and gas project in PNG. The aim of this study was to determine the geochemical profile of sediment cores of Lake Kutubu and to comprehend the contamination changes undergone in this lake due to mining activities utilising the hydraulic fracturing method. Sediment core profiles of Na, Mg, Al, Si, P, Ca, Ti, Cr, Fe, Mn, Ni, Cu, Zn, As, Se, Sr, Cd, Ba, Ce, Pb and U, grain size and dating analyses were conducted for five sites in the lake. Grain size and dating demonstrated that the northwest side of Lake Kutubu has sediments of allocthonous origin while the southeast sediments are of autochthonous origin. Ba was the element with the largest changes in concentrations since 1990 and the best tracer of mining activities near the lake. Sites KTB 02 and KTB 10 northwest of the lake showed the most distinct changes in element concentrations. Element enrichment factors (EF = 2.8, 4.2 and 3.2 respectively) demonstrated that Mn, Se and Ba have undergone a moderate enrichment in the lake since mining activities started. Ni, Cd and Se concentrations exceed sediment guidelines in some samples. No guideline is available for Ba, and special attention should be given to this element in this lake. This study demonstrated that Lake Kutubu oil/gas extraction activities are significant sources of elements to this lake and highlights the need for studies on the partitioning and speciation of elements to understand organism metal exposure. Highlights: Lake Kutubu is located within the largest oil and gas project facilities in PNG. Trace elements in lake sediments are related to mining and development activities. Ba is the best tracer of mining activities in sediments. Ba is the element of most concern in Lake Kutubu.